2012
DOI: 10.1097/lgt.0b013e3182562f1e
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Self-Reported Urinary, Gastrointestinal, and Pain Comorbidities in Women With Vulvar Lichen Sclerosus

Abstract: Objective-To determine the prevalences of comorbid disorders in women with vulvar lichen sclerosus. . Prevalences of self-reported comorbidities in our subjects are: OAB 15.3%, UI 38.6%, SUI 27.9%, IBD 1.9%, Constipation 32.5%, IBS 19.5%, Thyroid dysfunction 33.1%, IC 2.6%, Fibromyalgia 9.1%, TMJ 13.0%, Vulvar pain 83.1%. The prevalence of each disorder is significantly different than that in the general population, with all p values ≤ 0.02. Materials and Methods-Conclusions-Vulvar lichen sclerosus is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 28 publications
(16 reference statements)
7
22
1
4
Order By: Relevance
“…Thomas et al [16], considering the age at onset in 355 women with anogenital lichen sclerosus, found that 49% of cases occurred in women over 50 years of age and 42% occurred in the reproductive years, while among our patients an onset after 50 years of age was reported by 77.8% of patients and prior to 50 years only by 22.2%. Our findings seem to corroborate that the peak of incidence of VLS in adulthood is characteristically located within the postmenopausal years [17,18,19]. …”
Section: Discussionsupporting
confidence: 78%
“…Thomas et al [16], considering the age at onset in 355 women with anogenital lichen sclerosus, found that 49% of cases occurred in women over 50 years of age and 42% occurred in the reproductive years, while among our patients an onset after 50 years of age was reported by 77.8% of patients and prior to 50 years only by 22.2%. Our findings seem to corroborate that the peak of incidence of VLS in adulthood is characteristically located within the postmenopausal years [17,18,19]. …”
Section: Discussionsupporting
confidence: 78%
“…Vulvar LS has been associated with numerous bladder, bowel, and other pain comorbidities including dyspareunia, burning sensation, and dysuria. 4,5 Vulvar scarring often occurs, at times resulting in problems with intercourse. In patients with advanced disease, the introitus may become narrowed resulting in painful sexual intercourse or preventing intercourse altogether.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Studies have evaluated LS and pain showing a significant impact on a woman's quality of life. 5,[9][10][11][12][13][14][15][16][17][18][19][20] Limited data are available focusing specifically on the effect of LS on quality of life (QoL) and sexual function. Two studies have shown that patients with LS report significant impact on all major QoL domains (including those related to sexual issues) except school/studying and work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations